PSYCHOLOGICAL PROBLEMS OF TRAINING HIGHLY QUALIFIED PERSONNEL IN THE CONDITIONS OF GLOBALISATION. (Universal International Scientific Journal, 2026)
The digital transformation processes observed in the last decade — the introduction of artificial intelligence systems, algorithmic management, the platform economy, remote work formats, and the expansion of digital education ecosystems — are systematically reorganizing the structure and functional mechanisms of the labor market. These changes are not only updating the nomenclature of professions, but are also fundamentally transforming the psychological foundations of professional development. The modern work environment promotes flexibility over stability, and metacompetences over traditional competencies as a priority value [1. 42 p.].
Keywords: globalization, highly qualified personnel, psychological problems, professional development, competence, competitiveness, stress and adaptation, motivation, personal development, cognitive potential, emotional intelligence, professional identification, quality of education, innovative education, modern pedagogical technologies, intercultural communication, socio-psychological adaptation, leadership skills, creative thinking, continuing education.